Host Immune Response to Influenza A Virus Infection - Chen, Xiaoyong; Liu, Shasha; Goraya, Mohsan Ullah; Maarouf, Mohamed; Huang, Shile; Chen, Ji-Long (Frontiers in Immunology, 2018)
Influenza A viruses (IAVs) are contagious pathogens responsible for severe respiratory infection in humans and animals worldwide. Upon detection of IAV infection, host immune system aims to defend against and clear the viral infection. Innate immune system is comprised of physical barriers (mucus and collectins), various phagocytic cells, group of cytokines, interferons (IFNs) and IFN-stimulated genes (ISGs), which provide first line of defense against IAV infection. The adaptive immunity is mediated by B cells and T cells, characterized with antigen-specific memory cells, capturing and neutralizing the pathogen. The humoral immune response functions through hemagglutinin (HA) specific circulating antibodies to neutralize IAV. In addition, antibodies can bind to the surface of infected cells and induce antibody-dependent cell-mediated cytotoxicity (ADCC) or complement activation. Although there are neutralizing antibodies against the virus, cellular immunity also plays a crucial role in the fight against IAVs. On the other hand, IAVs have developed multiple strategies to escape from host immune surveillance for successful replication. In this review, we discuss how immune system, especially innate immune system and critical molecules are involved in the antiviral defense against IAVs. In addition, we highlight how IAVs antagonize different immune responses to achieve a successful infection.